Analgesic effect of Dahuang Fuzi Decoction in neuropathic pain through inhibiting TNF-α and PI3K-AKT signaling - Qu, Jinglian; Gong, Qian; He, Siyu; Peng, Jiuyan; Chen, Lingyan; Wang, Long; Chen, Peng (Frontiers in Neuroscience, 2024)
BackgroundNeuropathic pain (NeP) presents considerable challenges in terms of effective management and significantly impacts the quality of life for affected patients. The current treatment options for NeP are limited, highlighting the need for alternative therapeutic approaches. Dahuang Fuzi Decoction (DF), a formula from traditional Chinese medicine, has shown potential in relieving pain symptoms associated with various types of NeP. However, the mechanisms through which DF exerts its effects remain largely unknown.MethodsIn this study, we employed ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-HRMS) to analyze the chemical composition of DF. A chronic sciatic nerve compression injury (CCI) rat mode was used to assess the analgesic efficacy of DF for NeP. Network pharmacology analysis was performed to identify the potential signaling pathways affected by DF.ResultsDF treatment significantly increased the mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) in CCI rats, indicating its analgesic effect. Network pharmacology analysis suggested that DF potentially modulated TNF-α and PI3K-AKT signaling pathways. Furthermore, DF treatment decreased the levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in spinal cord tissues of CCI rats, suggesting an anti-inflammatory effect. Western blot analysis revealed that DF treatment reduced the expression of TNF-α, TNFR1, and phosphorylated forms of PI3K, AKT, IKKα/β, IKBα, and NF-κB in the spinal cord of CCI rats. Immunofluorescence analysis confirmed significant reductions in TNF-α and TNFR1 expression, as well as in AKT and NF-κB phosphorylation within astrocytes following DF administration.ConclusionOur findings characterize the chemical constituents of DF and elucidate its underlying mechanism for relieving NeP. The analgesic effect of DF involves the inhibition of TNF-α and PI3K-AKT signaling pathways, providing a potential therapeutic approach for NeP management.